2016
DOI: 10.1016/j.radonc.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Up-front neck dissection followed by definitive (chemo)-radiotherapy in head and neck squamous cell carcinoma: Rationale, complications, toxicity rates, and oncological outcomes – A systematic review

Abstract: Due to lack of well-designed randomized trials, it is difficult to assess the role of UFND in organ-preserving (C)RT setting of head and neck cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 96 publications
(231 reference statements)
0
16
0
2
Order By: Relevance
“…The need for upfront ND in the treatment of HNC is still a matter of debate. Recently, a systematic review on the subject concluded that few comparative studies suggest possible benefits of upfront neck dissection in the RT organ-preserving setting in terms of early toxicity and oncological outcome, although the level of evidence is very low [12]. Most studies on this subject have a low number of patients, do not contain information on HPV status and date from an era before concomitant CT treatment was common.…”
Section: Discussionmentioning
confidence: 99%
“…The need for upfront ND in the treatment of HNC is still a matter of debate. Recently, a systematic review on the subject concluded that few comparative studies suggest possible benefits of upfront neck dissection in the RT organ-preserving setting in terms of early toxicity and oncological outcome, although the level of evidence is very low [12]. Most studies on this subject have a low number of patients, do not contain information on HPV status and date from an era before concomitant CT treatment was common.…”
Section: Discussionmentioning
confidence: 99%
“…Such a heterogeneous behavior poses an obvious challenge to achieve simultaneous local (primary tumor) and regional (lymph node metastases) disease control. Indeed, while most early-stage (with the exception of oral squamous cell carcinoma) and some advanced-stage primaries can be usually managed by radiotherapy (with or without chemotherapy/cetuximab), presence of lymph node metastases often requires combined approaches, encompassing neck dissection and irradiation (3). Distant metastases develop in approximately 10%-30% of HNSCC patients after definitive therapy and carries a meager prognosis (approximately 5% overall 5-year survival; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Rescue or salvage surgery after concomitant treatment failure is associated with a high rate of postoperative complications 10 , and therefore it is preferable to perform lymph node dissection first in order to reduce morbidity. This is called "upfront neck dissection", which has the virtue of offering adequate staging and a lower rate of complications in comparison with rescue dissection 11 .…”
Section: Discussionmentioning
confidence: 99%